Attitudes Toward Caring of the Elderly From the Perspective of Nursing and Midwifery Students in Kermanshah Province in 2015 - Mohammad Mehdi Mohammadi; Masoumeh Esmaeilivand (University of Social Welfare & Rehabilitation Sciences, 2017)
Objectives Attitudes of health care providers towards patients can be an important underlying factor for providing efficient and effective care. Positive attitude of the nurses towards the patients coupled with more motivation and determination can be a mantra to better clinical services. The present study was conducted to determine the attitude of nursing students in relation to the care of the elderly. Methods & Materials This study is a descriptive study conducted on 211 students in Nursing and Midwifery, in Kermanshah Province, Iran in 2015. Data collection tool was a questionnaire consisting of 21 questions. Data analysis, including independent t test was done using SPSS 22. Results The mean (SD) age of the participating nursing students was 97.5 (63.72) and nurse practitioners 27.7 (6.74) years. There was a statistically significant difference (P <0.05). The majority of trainees (8.89%) and nurse practitioners (3.81%) had moderate approach to the care of the elderly. Items of ((nursing of the elderly is a waste of time because they have reached the end of his life)) from the perspective of Trainees 57.0 ± 67.4 and nurse practitioners 47.0 ± 73.4 had the highest average among the items that there was no significant difference between the two averages (P>0.05). Conclusion Although the majority of students have average attitude (not good) toward the elderly, it is felt that more specialized training is needed to improve knowledge and attitudes of aging. Considering that the nurse practitioners had a more positive attitude, teaching them is effective to create a positive attitude.